AB1020 Multifrequency bioimpedance combined with acoustic myography – a non-invasive pain-free assessment of muscle use. (15th June 2017) - Bartels, EM; Olsen, J Kvistgaard; Bliddal, H; Kristensen, LE; Danneskiold-Samsøe, B
Abstract : Background: Musculoskeletal diseases may involve muscle function, which often deteriorates due to a combination of pain and lack of exercise. Possible correction of this by training, or at least achievement of optimal efficiency of involved muscles with therapy, taking age and affecting disease into account, is an area which needs easily applicable and non-invasive pain-free assessment methods capable of monitoring daily living tasks outside a strict laboratory setting. Multi-frequency bioimpedance (mfBIA), assessing muscle health prior to exercise, in combination with Acoustic Myography (AMG), which allows real-time tests while e.g. walking or bicycling, may be such a method. Objectives: To validate AMG combined with mfBIA for muscle-use assessment during a series of daily activity movements and exercise with the aim of introducing the method in the clinic. Methods: 10 healthy subjects aged 25–68 years were assessed with mfBIA (Impedimed, Brisbane, Australia) prior to and following exercise of m. gastrocnemius during walking, stair climbing and descending, and cycling with increasing load. AMG was recorded with a CURO unit (MyoDynamik ApS, Frederiksberg, Denmark), and data handling was carried out with the software belonging to the devices. The mfBIA parameters considered were resistance (R), internal (Ri) and external (Re) resistance and centre frequency (fc), and the AMG parameters were Efficiency (E) – synchronization of motoric units, Temporal summation (T) – how frequently do you use a particular muscle fibre, and Spatial summation (S) – how many fibres in use at a given time, all given as Median; Min, Max. Results: The mfBIA data, showing the health state of the muscle, showed changes in R, Ri, Re and fc as expected for a healthy muscle as an effect of exercise. The AMG data showed good reproducibility with repeated measurements. Walking on flat ground was less synchronized (E 2; 1, 4) as were walking up (E 4; 1, 6) and down stairs (E 3; 1, 6), than cycling (E 8.5; 5, 9). With increasing load during cycling, E decreased with the higher demand to E 5.5 range 1–7. The T-score was similar around 7 for all types of walking, while overall decreasing with increasing load during cycling from 6.5 to 5.5. The S-score was low during the three types of walk, indicating use of many fibres (S around 3), which is in line with the low E-score. For cycling the S-score decreased slightly with increasing load, from 8 to 7.5. Conclusions: The combined method of mf-BIA and AMG shows good reproducibility. This method has the potential to assess training possibilities in patients with musculoskeletal diseases by testing directly on muscles during the movements of daily function. The method is applicable in real life settings outside the laboratory. Acknowledgements: The Parker Institute is supported by the OAK Foundation Disclosure of Interest: None declared